Schaum's outline of theory and problems of international economics - Salvatore, Dominick (New York : McGraw-Hill, 1995)
Schaum's Outlines present all the essential course information in an easy-to-follow, topic-by-topic format. You also get hundreds of examples, solved problems, and practice exercises to test your skills.
Keywords: International economic relations -- Outlines, syllabi, etc; International economic relations -- Problems, exercises, -- exercises, etc